PUSAT PELATIHAN KERJA DAN KETERAMPILAN UNTUK PENYANDANG DISABILITAS FISIK DI KOTA PONTIANAK - Muhammad Ishadi Zikri; Muhammad Ridha Alhamdani; Rudiyono Rudiyono (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
According to the Law of the Republic of Indonesia Number 8 of 2016 persons with disabilities are any person who experiences physical, intellectual, mental and or sensory limitations in the long term who in interacting with the environment can experience obstacles and difficulties to participate fully and effectively with other citizens. based on equal rights. These rights include the right to life, free from stigma, education, health, social welfare, accessibility, public services to employment, entrepreneurship and cooperatives. According to the Pontianak City Social Service, in 2021 people with disabilities in Pontianak City will number 1,161 people with 12 different types of disabilities. The most types of people with disabilities are physical disabilities, amounting to 276 people. Of the total number of people with disabilities in Pontianak City, only 34 people have jobs while the others are unemployed. The Job Training and Skills Center is a place that accommodates and facilitates all activities related to the process to become better than before by learning something to become an expert, clever and proficient in the field that is occupied. The design of the Job Training and Skills Center for Persons with Physical Disabilities is one of the facilities in fighting for the rights of Persons with Disabilities in Pontianak City and its surroundings. The design theme used is using a biophilic architecture approach with an emphasis on accessibility.